COMPETENCY-BASED CURRICULUM DEVELOPMENT TO IMPROVE JOB READINESS OF SECONDARY SCHOOL GRADUATES - Adi Mursalin; Ignatius Septo Pramesworo; Rosijanih Arbie (CV. ADIBA AISHA AMIRA, 2024)
In the face of dynamic and competitive labour market demands, education that is oriented towards practical learning outcomes is an inevitable necessity. The Competency-Based Curriculum (KBK) has been identified as a potential approach in preparing students to enter the world of work. This study aims to analyse the effectiveness of the implementation of the Competency-Based Curriculum in improving students' work readiness and identify the challenges faced in the implementation process. The research method used in this study was a literature review. The results show that the Competency-Based Curriculum can significantly improve students' work readiness by integrating competencies relevant to industry needs into the curriculum. This method emphasises the development of practical, critical and analytical skills through project-oriented learning and collaboration with industry. However, results also indicate challenges in resources, educator training, and the need for improved infrastructure and assessment methodologies to support effective implementation of KBK.